Power Plant Waste Heat Utilization for Soil Heating using Subsurface Pipes - Sabeeh Abed-Alkareem, Salah (Journal of Engineering and Sustainable Development, 2012)
Warm water is circulated through the soil medium in order to maintain the plant root zone above the same critical temperature. In power plants rejecting heat from steam through the condenser, the waste heat could be a suitable resource for soil heating. This work presents theoretical and numerical models. Two methods are applied with water temperature (20°C, 30°C, and 50°C) to give the temperature distribution in the soil around buried pipes carrying hot water. The Models used to calculate the required heated land area using the heat from power plants of Daura Steam Power Plant where the discharge 85000m3/hr at Tw = 20°C which is cover the land area (44.7Km2) with piping of (4cm) diameter and length of (10714m). The theoretical results are compared with experimental published work (Johnsion 1976) and showed good agreements.